Assessing the Impact of Substrate and Shelter on Cannibalism in Blue Swimming Crab (Portunus pelagicus) - Ariyati, Restiana Wisnu; Caesa, Genio; Rejeki, Sri; Hutabarat, Johannes; Haeruddin, Haeruddin; Sarjito, Sarjito; Widowati, Lestari Lakhsmi; Bosma, Roel (Jurnal Kelautan Tropis, 2024)
Blue swimming crab (Portunus pelagicus) is one of Indonesia’s essential fishery commodities, but overfishing has depleted its population. Aquaculture, as an alternative to produce this crab, is hampered by high levels of cannibalism. Substrates or shelters can reduce cannibalism. This study compared the effectiveness of one substrate and two types of shelter for reducing cannibalism of P. pelagicus crablets. Crablets with average carapace length of 3.6 ± 2.2 cm and average weight of 6.4 ±1.5 g.ind-1 were stocked in 24 rectangular tarpaulin tanks with 1 m2 surface and 50 cm water depth. The stocking density was 8 crablets in each tank. A split-plot experimental design was applied with four main plots and two subplots with 3 replications. The main plot consisted of A0 (without shelter), A1 (seaweed), A2 (pipes), and A3 (seaweed and pipes), and sub-plots had either no-substrate (B0) or sand-substrate (B1). Cannibalism (K), survival (S), and four water quality parameters were recorded for 42 days. The data were analyzed using an ANOVA for a split-plot design and post-hoc Tukey. The results show that the sand substrate significantly (P>0.05) reduced cannibalism and increased survival of the P. pelagicus. Treatment A0B0, without substrate or shelter, showed the highest cannibalism (54±7%) and lowest survival rates (33±7%). While treatment A1B1, with Gracillaria sp. as shelter and sand as bottom-substrate resulted in the lowest cannibalism (4±7%) and highest survival rates (88±13%).